IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT THROUGH THINK-PAIR-SHARE (TPS) TECHNIQUE - Nova Elisabeth Siahaan and Siti Aisah Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study attempts to improve students’ achievement in writing procedure text through Think-Pair-Share (TPS) technique. The result of writing test showed that the students score kept improving significantly. The mean of post-test I was 80,525 and the mean of post-test II was 92,98. The mean score of post-test II in cycle II was the highest. The mean of post-test I until post-test II increased significantly from 80,525 to 92,98. The students became active participants,  enjoyable, and enthusiatis in teaching and learning process through Think-Pair-Share (TPS) Technique. The result of the research showed the progress of achievement scores, it can be concluded that Think-Pair-Share (TPS) technique gives contribution to improve students’ achievement in writing procedure text.